New Venture Creation: Business Plan: Gamingdom-The gaming kingdom - Boban, Nitin; Sharma, Sourabh; Dharmapuri, Zatin (2010)
New Technology implementation is a never ending process and organizations try to utilize it in the best possible method for providing value and capturing value. New technology implementation can give way to innovation and development of new business models. This report is focused on providing high end gaming service via the web utilizing the cloud computing technology targeting the Indian Market initially, by three budding entrepreneurs. Cloud computing technology is a fast and growing technology where resources, software, storage and other aspects are provided on demand at a small price. An in-depth analysis of the gaming behavior and trend existing in India and the prospective growth fuelled this business plan. Online surveys and interviews were conducted to understand the market acceptance of the service and the technological challenges faced in implementing this business plan. Based on this an integrated marketing plan was developed which would be used to target the customer segment. Followed by a thorough scenario analysis, financial projections were made for the first three years of operation and then the future strategy of the business is discussed.